Peer review in teaching: the Strathmore experience - (:unkn) unknown (My University, 2015)
Peer reviewing is a process that has become popular around the world over the last 10-15 years. It can be used in different professional environments, as well as by students who make use of the collaboration of their peers to improve their academic performance. Given the parameters of this Conference, our paper focuses on peer review in the teaching context. Many third level institutions in the Western world are now using this method for evaluating the teaching performance of their academic staff. It is a system that has given rise to a lot of debate as many lecturers are not willing to have colleagues enter their class-room to analyse their teachings skills; at the same time, Faculties, Departments and Schools need to be able to evaluate the performance of their staff for various reasons. Searching the Internet one can find many sites that offer information, experience, and advice on how to create and implement a peer review system in teaching. In this paper we would like to transmit some experience that we have recently gained at Strathmore University regarding the peer review system in teaching.
Paper presented atRegional East African Unistaff Alumni 1st International Conference and Workshop on “Quality Assurance in Higher Education”, 6th – 10th November 2006 at Kenyatta University
Peer reviewing is a process that has become popular around the world over the last 10-15 years. It can be used in different professional environments, as well as by students who make use of the collaboration of their peers to improve their academic performance. Given the parameters of this Conference, our paper focuses on peer review in the teaching context. Many third level institutions in the Western world are now using this method for evaluating the teaching performance of their academic staff. It is a system that has given rise to a lot of debate1 as many lecturers are not willing to have colleagues enter their class-room to analyse their teachings skills; at the same time, Faculties, Departments and Schools need to be able to evaluate the performance of their staff for various reasons2. Searching the Internet one can find many sites that offer information, experience, and advice on how to create and implement a peer review system in teaching3. In this paper we would like to transmit some experience that we have recently gained at Strathmore University regarding the peer review system in teaching.
Keywords: Peer review; Teaching